Seleção assistida por marcadores moleculares de genótipos de tomateiro com altos teores de zingibereno para resistência a artrópodes-praga - Oliveira, João Ronaldo Freitas de (2018)
The development of pest-resistant cultivars has been expanded and it is indicated as an important strategy in their management. One of the great challenges of Brazilian tomatoculture is the control of pests, once the plant is susceptible to the attack of arthropod-pest, such as, Bemisia tabaci, Tuta absoluta¸ Diabrotica speciosa e Tetranychus urticae.In this article we aimed to select plants in the generation F2RC2 resulting from the crossing of Solanum. habrochaites var. hirsutum 'PI 127826' with the commercial cultivar Solanum lycopersicum cv. " Redenção ", based on the content of zingiberene that is a sesquiterpene present in leaflets of the wild plant S. habrochaites var. hirsutum that confers resistance to pest arthropods. There were selected in F2RC2 based on the zingibereno content of the genotypes, RVTZ 2011-79-503-pl#143, RVTZ 2011-79-503-pl#103, RVTZ 2011-79-503-pl#79, RVTZ 2011-79-335-pl#296, RVTZ 2011-79-335-pl#344, RVTZ 2011-79-335-pl#381, RVTZ 2011-79-335-pl#400, as being the closest statistically to the zingiberene content of S. habrochaites var hirsutum.In the present research were also used the molecular markers ISSR and SSR in order to characterize tomato genotypes with the largest portion of the recurrent genome.This work has a specific chapter of bioassays for pest resistance, where the host selection of arthropods of these four groups was evaluated: Lepidoptera (Tuta absoluta), Hemiptera (Bemisia tabaci), Coleoptera (Diabrotica speciosa) and Tetranychus urticae, aiming to characterize the resistance levels of genotypes with different levels of zingiberene. The selection assisted by molecular markers allowed the characterization of tomato genotypes with high levels of zingiberene with a higher rate of recovery of the recurrent genome of S. lycopersicum cv 'Redenção'.. The results obtained with the pest bioassays, suggest that the genotypes selected for the high zingiberene content RVTZ 2011-79-503-143, RVTZ 2011-79-335-164, RVTZ 2011-79-185-250, are potential sources of resistant genes against T. urticae, T.absoluta, B.tabaci and D. speciosa, for improving programs of the genetic of the tomato plants.